Relations of magnetic and electrochemical anti-corrosion properties of (Zr, Ti)-doped NdCeFeB magnets with Ti content - Yuxuan Shao; Junjie Ni; Zhiwei Wang; Xuegeng Wang; Kai Xu; Bo Song; Yue Xu; Shutai Zhou; Tao Liu; Laima Luo (Journal of Materials Research and Technology)
Zr and Ti were co-doped into NdCeFeB sintered magnets to improve the magnetic and electrochemical anti-corrosion properties. Both performance are found closely associated with Ti content. At 0.15 wt%Ti, the sample shows higher coercivity without energy product loss compared to the Ti-free sample and other Ti additions, due to the matrix-phases refinement and optimized distribution of RE-rich phases. For this sample, its corrosion current density and charge transfer resistance are 1.94 μA/cm2 and 1734 Ω•cm2 in NaCl solution respectively, which exhibits obviously improved corrosion resistance in comparison with the Ti-free magnet. The charge transfer resistance has been increased by 45.6 %. The apparently improved corrosion resistance is mainly attributed to the decreased amount of active reaction channels and the enhanced protective effect of TiO2, arising from the increment of Ti-rich precipitates. When the content of Ti dopant exceeds 0.5 wt%, the beneficial effects of Ti are overshadowed by the harmful effect of the density reduction on anti-corrosion performance, and the charge transfer resistance decreased with further increasing the dopant content. The new findings provide a theoretical basis for improving physicochemical properties of NdCeFeB magnet.